Friction of Mineralogically Controlled Serpentinites and Implications for Fault Weakness. Issue 8 (15th August 2018) - Tesei, T.; Harbord, C. W. A.; De Paola, N.; Collettini, C.; Viti, C.
Abstract: Serpentines are common minerals in several major tectonic faults in a variety of geodynamic settings and have variable frictional strength and complex deformation processes. Here we present friction experiments carried out on a suite of serpentine samples that include veins of antigorite, lizardite, and fibrous serpentine (chrysotile and polygonal serpentine) together with massive samples of retrograde (lizardite and chrysotile rich) and prograde (antigorite‐rich) serpentinites. These samples were characterized from the hand specimen down to the nanoscale to precisely constrain their mineralogical composition and are interpreted to represent typical fault rocks and host rocks in serpentine‐bearing shear zones, respectively. Experiments were performed at effective normal stress from 5 to 120 MPa, at temperatures of 25°C and 170°C and water‐saturated, that is, under the faulting conditions of the brittle upper lithosphere. Friction of antigorite samples, either massive or vein, is relatively high μ = 0.53. Retrograde, massive serpentinites, constituted primarily of lizardite and fibrous serpentines, are frictionally weak, μ = 0.30. End‐members lizardite and fibrous serpentines are even weaker, 0.15 < μ < 0.19, and this weakness is unchanged at high temperature. We document deformation of lizardite and fibrous serpentines occurring predominantly via mode II cracking, crystal/fiber folding, and frictional sliding, which account for the observed mechanical weakness. When combined with frictional reactivation analysis, our data provide mechanical evidence for fault weakness inferred from earthquake dip distributions at oceanic outer rises and low‐angle normal faults beneath rifted continental margins and at slow/ultraslow spreading mid‐ocean ridges. Key Points: We characterized the friction of serpentine serpentine samples that were carefully characterized from the mineralogical point of view Friction of lizardite and fibrous serpentines is low up to elevated temperature ( T = 170°C) The friction of lizardite and fibrous serpentines accounts for the observed weakness of several major faults